2013
DOI: 10.1080/14697688.2013.843786
|View full text |Cite
|
Sign up to set email alerts
|

Portfolio choice with indivisible and illiquid housing assets: the case of Spain

Abstract: This paper presents a procedure for computing the theoretically optimal portfolio under the assumption that housing is an indivisible, illiquid asset that restricts the portfolio choice decision. The analysis also includes the financial constraints households may face when they apply for external funding. The set of financial assets that constitute the household's portfolios are bank time deposits, stocks, mortgage, and housing. We compare the theoretically optimal portfolio against Spanish households' actual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Further, persistent borrowings from informal sources is also a serious concern that led researchers to focus on “debt” theme (Guérin et al , 2013). “Portfolio choice” started emerging during this period, as researchers started examining household decisions to invest in each asset class and their importance in household portfolio (Domínguez-Barrero and López-Laborda, 2012; Mayordomo et al , 2014). With growing interest in the field, “household balance sheets” became a niche theme.…”
Section: Thematic Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, persistent borrowings from informal sources is also a serious concern that led researchers to focus on “debt” theme (Guérin et al , 2013). “Portfolio choice” started emerging during this period, as researchers started examining household decisions to invest in each asset class and their importance in household portfolio (Domínguez-Barrero and López-Laborda, 2012; Mayordomo et al , 2014). With growing interest in the field, “household balance sheets” became a niche theme.…”
Section: Thematic Evolutionmentioning
confidence: 99%
“…Heimer et al (2019) find that mortality risk causes young people to under-save and retirees to draw down their savings slowly. Mayordomo et al (2014) have compared the optimal portfolio of households, conditional on housing value, with their actual portfolio and investigated the factors responsible for the deviation between both portfolios. Their results show that Spanish households invest less in deposits, stocks and mortgages than in optimal investments.…”
Section: Cluster 5: Life Cycle Approach and Portfolio Choicementioning
confidence: 99%
“…Despite the long-standing theoretical appeal of rational agents and the efficient market hypothesis, not all households enter the risky asset markets as the classical portfolio theory expects (Campbell, 2006). Researchers have demonstrated that background risk (Benzoni and Chyruk, 2009;Bonaparte et al, 2014), demographic characteristics (Guiso et al, 2002;Cardak and Wilkins, 2009), social interaction (Hong et al, 2004;Brown et al, 2008) and credit constrains (Mayordomo et al, 2014) can explain the stock market limited participation puzzle. The institutional environment plays a vital role in individuals' financial behavior.…”
Section: Introductionmentioning
confidence: 99%